2015
DOI: 10.1016/j.mspro.2015.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Porous Titanium Dioxide Coatings Obtained by Anodic Oxidation for Photocatalytic Applications

Abstract: The aim of this work is to obtain porous titanium dioxide with good efficiency for photocatalytic environmental applications. TiO 2 coatings were obtained by anodic spark deposition, at constant applied potential (150 V), using a platinum cathode and 0.5 M sulfuric acid as electrolyte. Samples of titanium Grade 2 were used as substrate, metallographically prepared until 1 μm diamond surface finishing. The variables of the process were temperature (25 and 40 °C) and anodization time (5 and 10 min). Samples obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Thereby, porous oxide layer will not be formed on the titanium anodised at higher bath temperature. Yetim [ 194 ] and Traid et al [ 195 ] also found that higher bath temperature leads to the reduction of porosity and thickness of TiO 2 anodic layer. Similarly, lower bath temperature also induces the formation of TiO 2 nanotubes with ideal packed hexagonal prisms.…”
Section: Factor Affecting Characteristics Of Tio 2 Layermentioning
confidence: 99%
“…Thereby, porous oxide layer will not be formed on the titanium anodised at higher bath temperature. Yetim [ 194 ] and Traid et al [ 195 ] also found that higher bath temperature leads to the reduction of porosity and thickness of TiO 2 anodic layer. Similarly, lower bath temperature also induces the formation of TiO 2 nanotubes with ideal packed hexagonal prisms.…”
Section: Factor Affecting Characteristics Of Tio 2 Layermentioning
confidence: 99%
“…literature [20]. This includes physical and chemical vapor deposition, anodic oxidation, atomic layer coating, magnetron sputtering, pulsed laser coating, electro deposition, dip coating [21][22][23][24][25][26][27][28][29]. Dip coating is in fact, one of the most popular methods.…”
Section: Tio 2 Immobilization In Photoreactorsmentioning
confidence: 99%
“…The electrochemical anodizing is a common surface modification method for Ti and its alloys where the work piece is used as anode in an electrolytic cell to form stable oxide coating [1][2][3][4][5][6][7][8]. The process can be performed under potentiostatic or galvanostatic mode in numerous electrolytes.…”
Section: Introductionmentioning
confidence: 99%